PHILOSOPHY OF INFORMATION AND TRANSHUMANISM: EXPLICATIONS OF PHILOSOPHICAL ANTHROPOLOGY - O. V. Marchenko; P. V. Kretov (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen', 2019)
Purpose. The research is aimed at finding out the grounds, forms and essence of the correlation between the projects of information philosophy and transhumanism from the point of view of the problematics of philosophical anthropology. Attention is focused on the status of the knowing subject and the transformations of the forms of its activity within the specified correlation. Theoretical basis. Insufficient thinking on the issue of the functioning of traditional cognitive models, in particular Kant’s transcendental questioning, which formed the basis of modern rationality and classical science, in the new sociocultural reality led the authors to problematize the forms and essence of interaction and operating with knowledge and communication in the information sphere of human existence and communication. A comparative consideration of the worldviews in the information philosophy and transhumanism projects, made on the basis of a study of current scientific literature, provided an opportunity to assume the probability of implicit elimination of the problems of philosophical anthropology from the horizon of meanings of modern science through the blurring of essentially anthropological analytics. Originality. The article proves the ambivalent nature of the correlation between the projects of philosophy and transhumanism information that are externally close on the subject and problematics, and for the first time in the domestic literature, they have been compared. The content of the powerful potential of information philosophy for the development of philosophical anthropology approaches to the phenomena of the human world determined by the technological nature of civilization and the powerful sociocultural issues of modernity have been clarified. The threats of the dehumanization of the problem field in the modern science and spheres of applied digital technologies associated with transhumanism, interpreted as an ideology, are underlined. Conclusions. The analysis of theoretical positions relevant for the philosophy of information and transhumanism resulted in a number of conclusions, central among which is the statement of the "blurring" situation, the hidden elimination in the content of problematics of philosophical anthropology and its humanistic pathos within the limits of modern forms of correlation and existence in the scientific discourse of the philosophemes and ideologemes in the information philosophy and transhumanism. Epistemological phenomena of "cognitive closure" and a man as a "blind spot" in the thinking on the science and technology development, primarily communication, indicate the relevance of a full comprehensive consideration of the problems of philosophical anthropology in projects of the information philosophy and transhumanism.